Double burden of malnutrition among adolescents: Evidence from a cross-sectional study among school-going adolescents in Bangalore city - Bhavya Balasubramanya; Avita Rose Johnson; T. Sulekha (Indian Journal of Health Sciences and Biomedical Research KLEU, 2024)
BACKGROUND: Previously, low- and middle-income nations grappled with widespread undernutrition, but now encounter the added challenge of overweight/obesity. Rapid urbanization has led to changes in the diet and physical activity of Indian adolescents. Malnutrition during adolescence has far-reaching consequences into adulthood. OBJECTIVE: The objective of this study was to assess the nutritional status of adolescents in schools and identify associated factors, with the aim of assessing whether the double burden of malnutrition exists among urban adolescents. METHODS: A cross-sectional study was conducted across four schools of Bangalore city with a universal sampling of 752 adolescents aged 10–19 years. Height and weight were entered into the WHO AnthroPlus software to compute body mass index-for-age and categorize nutritional status as per Z-scores. Sociodemographic details and data on diet and physical activity were collected by the interview schedule. The Chi-square test and Independent t-test were done to associate nutritional status with various exposure variables, followed by multiple logistic regression separately for undernutrition and for overweight/obesity. RESULTS: The prevalence of adolescent undernutrition was 13.3% (95% confidence interval [CI]: 10.89%–15.71%) and significantly associated with middle adolescence (odds ratio [OR] = 2.6 [1.43–2.75]), <8 h of sleep (OR = 1.68 [1.07–2.65]). The prevalence of overweight/obesity was 13.3% (95% CI: 10.89%–15.71%) and significantly associated with female gender (OR = 2.10 [1.33-3.31]), consumption of aerated drinks (OR = 2.35 [1.24–4.44]), and bakery products (OR = 1.68 [1.24–4.44]). CONCLUSION: Among urban school-going adolescents, there exists a double burden of malnutrition, with an equal proportion of undernutrition and overweight/obesity. Initiatives are needed to promote healthy eating and physical activity among adolescents, periodic health appraisals at school and enhancing the quality of meals at school and at home through health education and policy change.